2018
DOI: 10.1177/0271678x18769513
|View full text |Cite
|
Sign up to set email alerts
|

The intracerebral hemorrhage blood transcriptome in humans differs from the ischemic stroke and vascular risk factor control blood transcriptomes

Abstract: Understanding how the blood transcriptome of human intracerebral hemorrhage (ICH) differs from ischemic stroke (IS) and matched controls (CTRL) will improve understanding of immune and coagulation pathways in both disorders. This study examined RNA from 99 human whole-blood samples using GeneChip® HTA 2.0 arrays to assess differentially expressed transcripts of alternatively spliced genes between ICH, IS and CTRL. We used a mixed regression model with FDR-corrected p(Dx) < 0.2 and p < 0.005 and |FC| > 1.2 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 80 publications
0
63
0
2
Order By: Relevance
“…RNA-binding protein-mediated posttranscriptional regulation plays an important role in the pathophysiological processes of diseases (Wurth et al, 2016;Bar-Ziv et al, 2019;Baser et al, 2019). Recent studies have shown that posttranscriptional regulation is also associated with ICH (Dykstra-Aiello et al, 2015;Stamova et al, 2019). However, what roles RBPs play in ICH is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA-binding protein-mediated posttranscriptional regulation plays an important role in the pathophysiological processes of diseases (Wurth et al, 2016;Bar-Ziv et al, 2019;Baser et al, 2019). Recent studies have shown that posttranscriptional regulation is also associated with ICH (Dykstra-Aiello et al, 2015;Stamova et al, 2019). However, what roles RBPs play in ICH is still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Accessing posttranscriptional regulation is important to influence the occurrence and development of diseases, such as ICH (Dykstra-Aiello et al, 2015, 2016Stamova et al, 2019). Posttranscriptional regulation includes various processes, such as alternative splicing (AS) (Paschalis et al, 2018), alternative polyadenylation (APA) (Tian and Manley, 2017), gene expression regulation (Roundtree et al, 2017), and RNA methylation (Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time of sample collection ranged from 4.4 to 83.2 h after IS. Blood was drawn into PAX gene tubes (Qiagen) and stored frozen at −80°C until processed …”
Section: Methodsmentioning
confidence: 99%
“…Сравнение транскриптомов крови пациентов с ии и Ги выявило различия в экспрессии ряда факторов. Например, интерлейкины IL-1 и IL-17A, TGFα, HGF и гранулоцитарный колониестимулирующий фактор G-CSF активируются при Ги, но не при ии [115]. Повышенный сывороточный уровень ММР9 может быть точным биомаркером для прогнозирования возникновения церебрального вазоспазма после субарахноидального кровоизлияния [1].…”
Section: биомаркеры геморрагического инсультаunclassified